Online Supportive Conversations and Reflection Sessions (OSCaRS): A Feasibility Pilot with Care Home Staff during the Pandemic - Johnston, Lucy; Hockley, Jo; Watson, Julie; Shenkin, Susan D (International Journal of Practice-based Learning in Health and Social Care, 2022)
<span class="NormalTextRun SCXW19785442 BCX9" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"10a720ce-ca61-4ae4-bc77-d512b37f14b3|49","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Times New Roman",469777842,"Arial",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman,Arial",268442635,"20",335559685,"709",335559737,"425",335559740,"240",201341983,"0",335559739,"200",335551550,"6",335551620,"6",469777929,"Abstract Char",469775498,"Keywords",469778324,"Normal",469778325,"["Comments"]"]" data-ccp-parastyle-linked-defn=""ObjectId":"10a720ce-ca61-4ae4-bc77-d512b37f14b3|86","ClassId":1073872969,"Properties":[469775450,"Abstract Char",201340122,"1",134233614,"true",469778129,"AbstractChar",335572020,"1",134231262,"true",469777841,"Times New Roman",469777842,"Arial",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman,Arial",469777929,"Abstract",469778324,"Default Paragraph Font",469778325,"["Comments Char"]"]">Care homes care for people with complex needs, supporting them to the end of life and are now being seen as the ‘de facto’ hospice. Reflective debriefing for care home staff has been found to help support staff and provide an educative and communicative function when a resident dies. Pre-COVID-19, one of the authors had been conducting reflective debriefings face-to-face with care home staff but when COVID-19 struck, face-to-face sessions were impossible. An online format was developed with the aim of providing emotional support and practice-based learning in relation to death and dying through reflection. This study assessed the acceptability and feasibility of delivering online supportive conversations and reflective sessions (OSCaRS) on palliative and end of life care to care home staff during the pandemic. A mixed methods study design was undertaken in April to September 2020. Qualitative data comprised of digital recordings of sessions and semi-structured interviews with OSCaRS participants, managers and session facilitators. An online survey was sent to all staff and had a response rate of 12%. Eleven OSCaRS were conducted over ten weeks. Thirty-four staff members attended one or more sessions. Three overarching themes were identified from the data: pressures of working in a pandemic, practicalities of delivering online support and, practice development opportunities. Engaging care home staff in online structured supportive conversations and reflections in relation to death and dying is acceptable, feasible and valuable for providing support with the pressures of working in a pandemic. There is value for OSCaRS to continue as online sessions as they provide care home staff access to practice-based learning and support from professionals and allows specialists based in a range of settings to in-reach into care homes in an efficient way. Future implementation must consider the availability of sufficient devices with cameras to aid participation, timing and frequency of sessions to accommodate staff workflows, the engagement and support of managers and post-session support.